2012
DOI: 10.1155/2012/387428
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Related Lumbopelvic Pain: Listening to Australian Women

Abstract: Objective. To investigate the prevalence and nature of lumbo-pelvic pain (LPP), that is experienced by women in the lumbar and/or sacro-iliac area and/or symphysis pubis during pregnancy. Design. Cross-sectional, descriptive study. Setting. An Australian public hospital antenatal clinic. Sample population: Women in their third trimester of pregnancy. Method. Women were recruited to the study as they presented for their antenatal appointment. A survey collected demographic data and was used to self report LPP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
119
1
7

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(141 citation statements)
references
References 44 publications
14
119
1
7
Order By: Relevance
“…Previous reports (5,8) have shown that the presence of pain before pregnancy is a potential risk factor and, conversely, the practice of physical activity is a preventive factor (4). However, corroborating our findings, previous studies (3,6) found no association with previous physical activity or during pregnancy, but found a strong association with a previous history of pain.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Previous reports (5,8) have shown that the presence of pain before pregnancy is a potential risk factor and, conversely, the practice of physical activity is a preventive factor (4). However, corroborating our findings, previous studies (3,6) found no association with previous physical activity or during pregnancy, but found a strong association with a previous history of pain.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the majority (63.3%) of the pregnant women reported experiencing this pain daily, being graded to 50% of them as high intensity and moderate to severe low back disability to 56.9% of the sample. Characteristics of gestational low back pain may vary throughout pregnancy, and even in the same pregnancy from one pregnancy to another, because it is assumed to depend on the balance between perceived pain, limitation, and individual ability to seek coping strategies (6). Another study (8) stated that 73% of the pregnant women reported low back pain, most of them felt as a spike, with daily frequency, duration of at least one hour and average intensity around seven.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations